Penegakan Hukum dan Keadilan Restoratif dalam Kasus Penggelapan Dana Nasabah: Telaah Putusan No. 107/Pid.B/2022/PN.Pin - Hikma Awdina; Lilis Suryani; Moch. Alfatah Alti Putra (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
This study examines legal considerations and the application of law by judges in Decision No.107/Pid.B/2022/PN. Pin related to the case of falsifying payment documents as a means of embezzlement of customer funds. Using normative research methods, this study analyzes the verdict based on the statements of witnesses and defendants, evidence, indictments, and demands of the public prosecutor. The results of the study show that the criminal act is regulated in Article 374 of the Criminal Code Jo Article 64 Paragraph (1) of the Criminal Code. The defendant, Afri Anjas Situmeang, was found guilty of